Managing the Complexity of Critical Infrastructures A Modelling and Simulation Approach - Setola, Roberto; Rosato, Vittorio; Kyriakides, Elias; Rome, Erich (Studies in Systems, Decision and Control, 2016)
Complexity; Simulation and Modeling; Quality Control, Reliability, Safety and Risk; Communications Engineering, Networks